Risk Evaluation on Security Personnel Managing Illegal Detainees in a Makeshift Covid-19 Low Risk Quarantine and Treatment Centre - Rusli, Mohammad Farhan; Abd Rahman, Anita; Moideen, Mohd Arshil; Erlendawati Mohd Anuar; Mahabot, Fuad Ridha; Wan Mustapha, Wan Mohd Harith; Abd Samad@Mahmood, Md Anuar (IIUM Medical Journal Malaysia, 2022)
Background: The COVID-19 pandemic situation in Malaysia has resulted in a whole country approach where a newly built makeshift low risk Covid-19 treatment centre was chosen to house all COVID-19 positive illegal immigrants. In view of the desperate situation the detained illegal immigrants were in as the risks of them behaving aggressively, taking hostage, running away and escaping from the treatment centre were high this is the first time ever other governmental, non-governmental and security agencies worked alongside healthcare personnel in a biological hazard treatment centre while the clinical management was of no different than any other clinical setup in the country. Methodology: This is a semi-quantitative and integrated type of hazard identification, risk assessment and risk control (HIRARC) approach where it incorporates risk rating and severity rating to cover four elements, which are people, property, environment, and reputation. Total scores range from 1 to 25 and was further categorized into low, medium and high risk in a color-coded representation. The assessment was done for two weeks from 27th May 2020 till 11th June 2020. Result & Discussion: Four types of occupational and security hazards identified were physical, biological, psychological and ergonomics hazards. this evaluation serves as a good planning tool in optimizing the risk mitigation measures among security personnel working in a biological hazardous environment. Physical hazards with possible violence and riot scored the highest risk while ergonomic issues had the lowest rating. Conclusion: The mapping combination of existing hazard, risk rating and control was able to facilitate organization to prioritise future planning. With the fluidity of the COVID-19 pandemic, periodical evaluation is recommended to meet dynamic changes such as demands for frontliner manpower strength, the number of existing detainee patients in ward and the evolution of the COVID-19 infection itself to maintain safety and security for all.